The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Les Amériques créatives: regards croisés sur les discours et les pratiques - Pujol, Charlotte; Doré, Émilie; Drouilleau, Félicie; Villafuerte, Susana; Tinteroff Gil, Vanessa (Recherches & documents Amérique latine, 2017)
"Des civilisations précolombiennes à l'American Way of Life, les A mériques ont constitué un espace propice aux mythes et aux utopies. Terres de migrations, parfois forcées, elles sont constituées de multiples lieux de rencontres, de conflits, d'échanges culturels. Aujourd'hui les phénomènes d'innovation technologique, identitaire ou politique témoignent du fait que les Amériques, du Nord au Sud, demeurent un terreau de créativité. La créativité repose sur la capacité des acteurs à imaginer un autre cadre que celui dans lequel ils sont immergés. Aussi cet ouvrage s'attarde-t-il sur les discours et les pratiques individuels ou collectifs, discrets ou médiatisés, improvisés ou programmés qui participent à la fabrique des espaces et des sociétés. La diversité des regards et des situations analysées se traduit par la multi disciplinarité de ces pages. Sociologues, anthropologues, historiens, juristes, géographes, spécialistes de la littérature, du cinéma, du théâtre ou de la musique proposent des analyses ancrées dans la réalité ; leurs points de vue sont autant d'illustrations des processus créatifs. Il ne s'agissait pas là de chercher une improbable exhaustivité, mais bien plutôt de tenter de mettre en lumière la façon dont la force créative des individus et des groupes jalonne l'histoire et le devenir des nations américaines. C'est donc un kaléidoscope qui est proposé aux lecteurs, une diversité d'approches qui les font voyager de l'Alaska au Brésil."--Page 4 de la couverture
Keywords: DIG; agriculture; amériques; anthropologie; arts; care; corps; cours; création; danse; discipline; environnement; géographie; musique; pol4022; premier cycle; régions géographiques; sciences humaines; sociologie; thématiques

Les Autochtones au Canada: espaces et peuples en mutation - Desbiens, Caroline; Hirt, Irène (L'Information géographique, 2012)
Alors que les questions relatives à l’autochtonie ont longtemps été le domaine de l’anthropologie, nous assistons ces dernières années à un décloisonnement des recherches. La géographie participe activement à cette mouvance, notamment par la richesse de sa boîte à outils en ce qui concerne les questions de paysage, ressources, environnement et gouvernance territoriale. En commençant par un survol des aires culturelles autochtones en Amérique, nous proposons dans cet article d’identifier trois thèmes dominants en ce qui a trait aux espaces de l’autochtonie contemporaine au Canada : la gouvernance, les savoirs, et l’urbanité.
Keywords: amériques; approches et analyses; cours; discipline; géographie; har4600; histoire et politique; pol4105; premier cycle; premières nations; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres